The effect of aerobic training and green tea supplementation on some of cardiovascular risk factors in obese men - امیرحسین حقیقی; علیرضا رفیعی پور; سید علیرضا حسینی کاخک (Shahid Beheshti University, 2011)
Objective: This study intends to examine the effect of aerobic training and green tea supplementation onsome of cardiovascular risk factors such as serum C-reactive protein, LDL, HDL, Total cholesterol andTriglyceride in overweight men. Methods: 43 overweight men were volunteered and were included infour groups: control group; green tea supplement group; exercise group and the exercise and green teasupplement group. Then, the experimental group performed the aerobic training program for 10 weeks,three sessions per weeks with intensity of 65 to 75% of maximum heart rate. Green tea group consumeddaily three green tea bags with 2grm tea content. The combined exercise and green tea group twointerventions took. Before and after the investigation period, blood sampling of all subjects were taken infasting. The data were analyzed by using one way ANOVA and ANCOVA tests. Results: Resultsshowed that aerobic trainings, green tea and combination of aerobic training and green tea have not asignificantly effect on serum C-reactive protein and lipid profile levels in obese men (P<0.05). Green teacaused a significant decrease in weight and body mass index (P<0.05). Aerobic training caused asignificant decrease in weight, body mass index and body fat percentage (P<0.05). Combination ofaerobic training and green tea caused a significant increase in maximal oxygen consumption andsignificant decrease in weight, body mass index and body fat percentage (P<0.05). There were nosignificant difference between the effect of green tea supplementation and aerobic training on decrease inweight and body mass index (P<0.05). Conclusion: We concluded that performing of aerobic trainingsand green tea supplement have not a significantly effect on cardiovascular risk factors in overweight men.But it can improve body composition and aerobic capacity in these volunteers. However, to achieve moreconclusive results, further investigation is warrented.